Analisis Perencanaan Obat Antibiotik Dengan Metode ABC Di Instalasi Farmasi RSUD Ir. Soekarno Sukoharjo - Yunika Yusup Sulistyowati; Susi Endrawati; Cipto Priyono (Indonesian Journal on Medical Science, 2022)
Drug planning is an effort to determine the type, quantity, and quality of drugs according to needs. Antibiotics are used as the main therapy in cases of bacterial infection, so good planning is needed to control their supply. This study aims to 1) determine the planning system for outpatient and inpatient antibiotic oral drugs at the Pharmacy Installation of RSUD Ir.Soekarno, adjusted to the Regulation of the Minister of Health No.72 of 2016, concerning pharmaceutical service standards in hospitals. 2) knowing the ABC analysis in planning outpatient and inpatient antibiotic oral drugs at the Pharmacy Installation.This study is a descriptive study with retrospective data collection on quantitative data using Microsoft Excel 2010.The data were obtained from items of oral antibiotics and the use of the period October-December 2020 and the purchase price of the drug. The data were analyzed using the ABC method. The results of the study list of oral antibiotics contained 26 items. Antibiotic group A consisted of 6 items, B consisted of 6 items, C consisted of 14 items. Conclusion: the planning system for oral antibiotics is in accordance with the Regulation of the Minister of Health No. 72 of 2016, concerning pharmaceutical service standards. Analysis of planning for oral antibiotics for outpatient and inpatient at pharmacy installations for the period October-December 2020, which is included in group A, absorbs a budget of Rp. 19,179,250.10 (70%), group B Rp 5,582,700.00 (20%), group C Rp. 2,684,764.60 (10%) of the total total budget.